Outcome of Chair-Side Dental Fear Treatment: Long-Term Follow-Up in Public Health Setting - T. Kankaala; T. Määttä; M. Tolvanen; S. Lahti; V. Anttonen (International Journal of Dentistry)
Aim. Purpose of this practice and data-based study was to evaluate the outcome of dental fear treatment of patients referred to the Clinic for Fearful Dental Patients (CFDP) in the primary oral health care, City of Oulu, Finland, during period 2000–2005. Methods. A psychological approach including behavioral interventions and cognitive behavioral therapy (BT/CBT) was used for all participants combined with conscious sedation or dental general anesthesia (DGA), if needed. The outcome was considered successful if later dental visits were carried out without any notifications in the patient records of behavioral problems or sedation. Data collection was made in 2006; the average length of the observation period from the last visit in the CFPD to data collection was 2 y 3 m (SD 1 y 5 m). All information was available for 163 patients (mean age 8.9 y at referral). Study population was dominated by males (58.0%). Cause for referrals was mostly dental fear (81.0%) or lack of cooperation. Results. The success rate was 69.6% among females and 68.1% among males. Success seemed to be (p=0.053) higher for those treated in ≤12 years compared with the older ones. The participants, without need for dental general anesthesia (DGA) in the CFDP, had significantly a higher success rate (81.4%) compared with those who did (54.8%, p<0.001). Use of conscious oral sedation (p=0.300) or N2O (p=0.585) was not associated with the future success. Conclusions. A chair-side approach seems successful in a primary health care setting for treating dental fear, especially in early childhood. Use of sedation seems not to improve the success rate.